Raman and infrared investigations of glass and glass-ceramics with composition 2Na2O·1CaO·3SiO2 - Ziemath, Ervino C. [UNESP]; Aegerter, Michel A. [UNESP] (Materials Research Society, 1994)
Precursor glass and glass-ceramics with molar composition 2Na2O·1CaO·3SiO2 are studied by infrared, conventional, and microprobe Raman techniques. The Gaussian deconvoluted Raman spectrum of the glass presents bands at 625 and 660 cm-1, attributed to bending vibrations of Si-O-Si bonds, and at 860, 920, 975, and 1030 cm-1, attributed to symmetric stretching vibrations of SiO4 tetrahedra with 4, 3, 2, and 1 nonbridging oxygens, respectively. The Raman microprobe spectrum of a highly crystallized sample presents two narrow and intense bands at about 590 and 980 cm-1, associated with vibrations of SiO4 tetrahedra with two nonbridging oxygens, in agreement with the predicted chain-like structure of crystalline metasilicates. Scanning electron microscopy shows that the crystals distributed in partially crystallized samples have a spherical shape, built up by radially oriented needle-like single crystals. The Raman microprobe spectra of these spherulites show that they still contain residual amorphous material. A comparison of Raman and infrared spectra of amorphous and highly crystallized samples is presented.
Keywords: Amorphous materials; Band structure; Ceramic materials; Crystal orientation; Crystals; Infrared spectroscopy; Molecular structure; Molecular vibrations; Raman spectroscopy; Scanning electron microscopy; Spectrum analysis; Bending vibrations; Glass ceramics; Glass